Gondang Batak di Era Digital: Tantangan Inkulturasi dan Strategi Pelestarian dalam Liturgi Huria Kristen Batak Protestan (HKBP) - Richi Holmes Pinondang Malau (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Gondang Batak serves as a symbolic-liturgical medium for the Batak community, deeply integrated into the worship system of Huria Kristen Batak Protestan (HKBP) since the mid-20th century. However, the digital era, marked by streaming platforms and algorithmic curation, has shifted music consumption from physical communal presence to personal digital spaces, threatening intergenerational transmission of gondang knowledge among the youth. This study aims to comprehensively describe current liturgical practices, systematically analyze various digital challenges, and formulate effective preservation strategies. Employing a qualitative ethnographic approach, it utilizes literature reviews, in-depth interviews with church leaders, and participatory observations in HKBP services. Findings indicate that gondang usage is primarily restricted to special festive celebrations, varies by location, and reveals significant generational gaps in appreciation. Key digital challenges include increasingly shifting youth preferences toward modern worship music, fierce competition on streaming platforms, and potential distortion of sacred meanings through commercialization. In response, HKBP has initiated musician training and digital archiving. This research recommends a critical inculturation liturgical model preserving theological integrity, alongside a digital marketing strategy using social media. Ultimately, preserving gondang is a theological imperative to incarnate the Gospel within Batak tradition, ensuring that rich cultural heritage and vibrant liturgical renewal coexist dynamically in contemporary worship.